Self‐Limited Epitaxial Growth of Patterned Monolayer Organic Crystals for Polarization‐Sensitive Phototransistor with Ultrahigh Dichroic Ratio - Chen, Jinhui; Wang, Jinwen; Chen, Shuai; Pan, Jing; Jia, Ruofei; Wang, Chaoqiang; Wu, Xiaofeng; Jie, Jiansheng; Zhang, Xiujuan (Advanced functional materials, 2024)
Monolayer organic crystals provide an unprecedented opportunity for studies on the intrinsic charge transport of organic semiconductors because of their 2D nature that is free of grain boundaries with fewer defects. However, due to the spatially stochastic molecular nucleation and the difficulty in controlling monolayer assembly, large‐scale growth of monolayer organic crystals remains a formidable challenge. Here, a self‐limited epitaxial growth strategy is proposed to realize large‐area patterned growth of monolayer organic crystals via physical vapor deposition process. Specifically, this approach confines the molecular nucleation and crystallization in defined wetting patterns, whose sizes are smaller than the mean free path of the molecules on substrate, enabling the formation of a single nucleus in wetting pattern. Meanwhile, the intermolecular lattice mismatch between 2,7‐dialkyl[1]benzothieno[3,2‐b][1]benzothiophene (Cn‐BTBT, n = 8 and 10) derivatives inhibits vertical molecular stacking, thereby promoting the monolayer assembly of organic molecules. Using this approach, centimeter‐sized patterned growth of mixed Cn‐BTBT monolayer organic crystals is achieved. Polarization‐sensitive phototransistors based on the monolayer organic crystals exhibit ultrahigh dichroic ratio up to 4.6 × 103, on par with the commercial polarizers (103). This work sheds light on large‐scale patterned growth of monolayer organic crystals toward high‐performance optoelectronic devices. A self‐limited epitaxial growth strategy is developed for large‐area patterned growth of monolayer organic crystals. This approach confines the molecular nucleation and crystallization in defined wetting patterns. Intermolecular lattice mismatch between C8‐BTBT and C10‐BTBT inhibits the vertical molecular stacking, promoting the monolayer assembly. Polarization‐sensitive phototransistors based on the monolayer organic crystals exhibit an ultrahigh dichroic ratio of 4.6 × 103.